Isolation and characterization of a thermophilic chain elongating bacterium that produces the high commodity chemical n-caproate from polymeric carbohydrates. (January 2023) - Van Nguyen, Tinh; Viver, Tomeu; Mortier, Jonah; Liu, Bin; Smets, Ilse; Bernaerts, Kristel; Faust, Karoline; Lavigne, Rob; Poughon, Laurent; Dussap, Claude-Gilles; Springael, Dirk
Graphical abstract: Highlights: MDTJ8 was isolated from a thermophilic anaerobic bioreactor producing n -caproate. MDTJ8 might be a novel bacterial species/genus within the family Oscillospiraceae. MDTJ8 produces n -caproate from polymeric saccharides via the RBO pathway. MDTJ8 is the first axenic bacterium that thermophilically performs chain elongation. Abstract: A thermophilic chain elongating bacterium, strain MDTJ8, was isolated from a thermophilic acidogenic anaerobic digestor producing n -caproate from human waste, growing optimally at 50–55 °C and pH 6.5. 16S rRNA gene analysis suggests that MDTJ8 represents a new species/genus within a group currently composed of mesophilic chain elongators of the Oscillospiraceae family. Genome analysis showed that strain MDTJ8 contains homologues of genes encoding for chain elongation and energy conservation but also indicated n -caproate production from carbohydrates including polymeric substances. This was confirmed by culturing experiments in which MDTJ8 converted, at pH 6.5 and 55 °C, mono-, di- and polymeric carbohydrates (starch and hemicellulose) to n -caproate reaching concentrations up to 283 mg/L and accounting for up to 10 % of the measured fermentation products. MDTJ8 is the first axenic organism that thermophilically performs chain elongation, opening doors to understand and intensify thermophilic bioprocesses targeting anaerobic digestion towards the production of the value-added chemical n -caproate.